Pengaruh komposisi lanskap pertanian terhadap kelimpahan, tingkat serangan, dan parasitisme Spodoptera frugiperda (Smith): Effect of agricultural landscape composition on abundance, attack rate, and parasitism of Spodoptera frugiperda (Smith - Sataral, Mihwan; Tawakkal, Muhammad Iqbal; Winasa, I Wayan; Triwidodo, Hermanu; Rizali, Akhmad; Buchori, Damayanti (Perhimpunan Entomologi Indonesia, 2024)
Landscape management in an agroecosystem is part of an ecological approach aimed at conserving biological control to suppress the abundance of pests and crop damage. This study investigates how agricultural landscape composition influences the abundance and attack rates of Spodoptera frugiperda and its parasitoids’ abundance and parasitism rates. The research assessed landscape characteristics in maize fields around Bogor, including class area (CA) and the number of patches (NP) of agricultural and semi-natural habitats. A 300-meter radius buffer was used to evaluate these features. Eggs and larvae of S. frugiperda were collected and reared in the laboratory to observe their parasitized and non-parasitized development. The influence of landscape composition on the abundance, attack rate, and parasitism of S. frugiperda was analyzed using generalized linear models. The results indicate that landscape composition affects the abundance and attack rate of S. frugiperda and influences the abundance and parasitism rate of parasitoids. Increasing the agricultural class area can increase the abundance of S. frugiperda larvae. In addition, increasing the NP and CA of semi-natural habitats can reduce the infestation rate of S. frugiperda. The elevation of maize areas also shows an influence on the abundance of parasitoids and the parasitism of larvae. In contrast, the age of the maize affects the abundance and attack of S. frugiperda. These findings highlight the importance of landscape composition, particularly the presence of semi-natural habitats, in managing pest populations effectively. This ecological approach offers valuable insights for sustainable pest control strategies in agricultural practices.